1987
DOI: 10.1002/1097-0142(19871101)60:9<2146::aid-cncr2820600904>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Acute monocytic leukemia in children: Response to VP-16-213 as a single agent

Abstract: Three patients were studied: two infants with acute monocytic leukemia who failed to respond to the initial combination therapy of daunorubicin with cytosine arabinoside, and an adolescent with relapsed acute monocytic leukemia. They were intensively treated with epipodophyllotoxin (VP-16-213) alone and subsequently had complete remission. One patient showed apparently dose-dependent cytotoxic effect. All three patients have maintained complete remission for 6, 7, and 11 months, respectively. Toxicities, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…There have been reports that VP16 has specific activity in acute monocytic leukemia. 29,30 For AraC, we found that, when comparing median values, M0 was more resistant than any other subtype; however, the difference was only significant against M4 (P = 0.016). The relationship between the biological characteristics classified by the FAB subtypes and AraC metabolism requires further research.…”
Section: Discussionmentioning
confidence: 82%
“…There have been reports that VP16 has specific activity in acute monocytic leukemia. 29,30 For AraC, we found that, when comparing median values, M0 was more resistant than any other subtype; however, the difference was only significant against M4 (P = 0.016). The relationship between the biological characteristics classified by the FAB subtypes and AraC metabolism requires further research.…”
Section: Discussionmentioning
confidence: 82%
“…This difference in the prognostic impact of M4 and M5 subtypes could be due to the use of different treatment regimens. Our treatment protocols included the epipodophyllotoxins, which are highly effective against M5 leukemia in infants 34,35 and in recent years they also incorporated 2-chlorodeoxyadenosine, an agent which appears particularly effective against M5 AML (RC Ribeiro, unpublished observation). While male gender is a recognized adverse feature in childhood ALL, 36,37 it generally lacks prognostic significance in studies of AML.…”
Section: Discussionmentioning
confidence: 99%
“…Repetitive cycles or postinduction courses of HD-AraC have been effective for AML. 21,22 Regimens including etoposide are also highly effective against acute monoblastic leukemia, 23,24 which is frequently seen in infant AML. In children with AML who were treated with the same protocol, the diseasefree survival rate was 62.4%, 25 which was also superior compared with the findings of other studies of childhood AML (EFS rate was 34%-43%).…”
Section: Discussionmentioning
confidence: 99%